Comparison of Thyroid Hormone Levels Between Patients With Major Depressive Disorder and Healthy Individuals in China - Zhou, Yanan; Ma, Yuejiao; Wu, Qiuxia; Wang, Qianjin; Yang, Winson Fu Zun; Wang, Yunfei; Yang, Dong; Luo, Yinli; Tang, Kewei; Liu, Tieqiao; Wang, Dongfang (Frontiers in Psychiatry, 2021)
Abnormal thyroid function in major depressive disorder (MDD) has been studied extensively, but the results still remain inconsistent. In China, few large-scale studies have investigated the differences in the levels of thyroid hormones between patients with MDD and healthy controls (HCs). In this retrospective, cross-sectional study, 535 MDD patients and 998 HCs were included. We compared the levels of thyroid hormones (FT3, FT4, and TSH) between the two groups, as well as investigated the distribution of levels of thyroid hormones within and outside normal ranges. The results showed that all the three hormones were significantly lower in MDD patients than in HCs, which was also true in different gender and age subgroups. The proportion of subjects with levels of all the three hormones outside the normal range in the MDD group was higher than that in the HC group (all p < 0.05). However, no significant difference was found in clinical/subclinical hyperthyroidism or hypothyroidism between the two groups (p > 0.05). Our study showed that the levels of thyroid hormones were lower in MDD patients, suggesting that there was an association between abnormal thyroid function and depression. The higher rate of thyroid dysfunction in MDD patients indicated the importance of regular monitoring of thyroid function.